2020
DOI: 10.1158/1078-0432.ccr-19-2958
|View full text |Cite
|
Sign up to set email alerts
|

FS222, a CD137/PD-L1 Tetravalent Bispecific Antibody, Exhibits Low Toxicity and Antitumor Activity in Colorectal Cancer Models

Abstract: Purpose: With the increased prevalence in checkpoint therapy resistance, there remains a significant unmet need for additional therapies for patients with relapsing or refractory cancer. We have developed FS222, a bispecific tetravalent antibody targeting CD137 and PD-L1, to induce T-cell activation to eradicate tumors without the current toxicity and efficacy limitations seen in the clinic. Experimental Design: A bispecific antibody (FS222) was developed by engineering CD137 antigen-binding sites into the Fc … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…The response rate to anti-PD-1 antibody treatment in ovarian cancer nearly triples when a CTLA-4 blocking antibody is added to the treatment regimen 37 . Furthermore, agonizing CD137 may aid in promoting antitumor responses in patients, and although CD137 agonism in the clinic has had toxicities 33,34 , dual bispecific antibodies that agonize CD137 are being developed in order to enhance T cell proliferation and antitumor activity in human cancer without the safety limitations observed in the clinic 35,36 . The recently developed CD137/OX40 bispecific antibody 35 may be promising to test in an ovarian cancer model, as we observed that effector molecule expressing CD137 + TILs also co-expressed OX40 ( Figure 2A ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response rate to anti-PD-1 antibody treatment in ovarian cancer nearly triples when a CTLA-4 blocking antibody is added to the treatment regimen 37 . Furthermore, agonizing CD137 may aid in promoting antitumor responses in patients, and although CD137 agonism in the clinic has had toxicities 33,34 , dual bispecific antibodies that agonize CD137 are being developed in order to enhance T cell proliferation and antitumor activity in human cancer without the safety limitations observed in the clinic 35,36 . The recently developed CD137/OX40 bispecific antibody 35 may be promising to test in an ovarian cancer model, as we observed that effector molecule expressing CD137 + TILs also co-expressed OX40 ( Figure 2A ).…”
Section: Discussionmentioning
confidence: 99%
“…The recently developed CD137/OX40 bispecific antibody 35 may be promising to test in an ovarian cancer model, as we observed that effector molecule expressing CD137 + TILs also co-expressed OX40 ( Figure 2A ). Future studies are needed to determine if CD137 + TILs are reinvigorated by anti-PD-1 therapy, whether they require CD28 signaling, and how they contribute to successful immune checkpoint blockade monotherapy or combinatorial immunotherapy strategies 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, co-targeting with natural co-stimulatory ligands or mAb agonists of co-stimulatory receptors is of interest because of its potential to provide signal 2 for full T cell activation. In this regard, interesting bispecific agents have been developed that integrate anti-fibroblast activated protein (FAP) 221 or anti-PD-L1 antibodies 222 (for tumour targeting) with the receptor-binding regions of CD137 ligand (for co-stimulation of T cells via binding to CD137). One such agent has already entered clinical testing in combination with the anti-PD-L1 antibody atezolizumab (NCT03869190); however, combination with CD3-targeted BiTEs is perhaps a more relevant approach following the observation of potent synergy in preclinical xenograft models 221 .…”
Section: Dual Tumour and Immune Targetingmentioning
confidence: 99%
“…One strategy to reduce their liver-related on-target effects has been to optimize FcγR binding to FcγRs that are normally enriched in tumors, 16 but next-generation bispecific antibodies have an advantage through crosslinking 4-1BB receptors only in the presence of tumor-associated antigens (TAAs) through cross-bridging, and various programs are currently entering the clinic targeting TAAs such as epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 (HER2). [19][20][21][22] PD-L1 (CD274, B7-H1), one of the ligands for PD-1, is a checkpoint regulator that restrains T cell activation during antigen presentation and effector function. PD-L1 expression has been identified in a wide variety of solid tumors, which makes it a potential TAA for PD-L1/4-1BB bispecific antibody development.…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1/4-1BB bispecific antibodies could therefore combine PD-L1 blockade and 4-1BB agonism to provide a substantial survival benefit in multiple mouse tumor models with low/ no toxicity. 22 Here, we report the discovery and development of a bispecific antibody towards PD-L1 and 4-1BB (PM1003). PM1003 potently blocks the interaction between PD-1 and PD-L1 and binds to 4-1BB at the CRD4 domain allowing for effective dose-dependent activation of 4-1BB in the presence of PD-L1, with minimal toxicity.…”
Section: Introductionmentioning
confidence: 99%